Identification of a New Equid Herpesvirus 1 DNA Polymerase (ORF30) Genotype with the Isolation of a C(2254)/H(752) Strain in French Horses Showing no Major Impact on the Strain Behaviour - Sutton, Gabrielle (Viruses, 2020)
Equid herpesvirus 1 is one of the most common viral pathogens in the horse population and is associated with respiratory disease, abortion and still-birth, neonatal death and neurological disease. A single point mutation in the DNA polymerase gene (ORF30: A2254G, N752D) has been widely associated with neuropathogenicity of strains, although this association has not been exclusive. This study describes the fortuitous isolation of a strain carrying a new genotype C(2254) (H(752)) from an outbreak in France that lasted several weeks in 2018 and involved 82 horses, two of which showed neurological signs of disease. The strain was characterised as U(L) clade 10 using the equid herpesvirus 1 (EHV-1) multi-locus sequence typing (MLST) classification but has not been identified or isolated since 2018. The retrospective screening of EHV-1 strains collected between 2016 and 2018 did not reveal the presence of the C(2254) mutation. When cultured in vitro, the C(2254) EHV-1 strain induced a typical EHV-1 syncytium and cytopathic effect but no significant difference was observed when compared with A(2254) and G(2254) EHV-1 strains. An experimental infection was carried out on four Welsh mountain ponies to confirm the infectious nature of the C(2254) strain. A rapid onset of marked respiratory disease lasting at least 2 weeks, with significant virus shedding and cell-associated viraemia, was observed. Finally, an in vitro antiviral assay using impedance measurement and viral load quantification was performed with three antiviral molecules (ganciclovir (GCV), aciclovir (ACV) and aphidicolin (APD)) on the newly isolated C(2254) strain and two other A/G(2254) field strains. The three strains showed similar sensitivity to ganciclovir and aphidicolin but both C(2254) and A(2254) strains were more sensitive to aciclovir than the G(2254) strain, based on viral load measurement.